Tindak Tutur Ekspresif dalam Tuturan Komentator E-Sports pada Turnamen PMCO Fall Split Global Finals 2019: Kajian Sosiopragmatik - Hardi, Sigian; Pastika, I Wayan; Dhanawaty, Ni Made (Stilistika : Journal of Indonesian Language and Literature; Vol 1 No 2 (2022): Volume 1 No. 2. April 2022, 2022)
The task of a commentator is to provide comments related to the course of the match. In his speech, Indonesian commentators in the 2019 PMCO Fall Split Global Final tournament included natural speeches that contained pragmatic elements, namely expressive speech acts. In addition, in reviewing matches, commentators use a lot of special vocabulary as a characteristic of the E-sports branch to interpret the actions taken by the players during the match. This study aims to describe the form and function  E-sports commentators in the 2019 PMCO Fall Split Global Final tournament and describe the special vocabulary used by E-sports commentators in the 2019 PMCO Fall Split Global Final tournament. This type of research is descriptive-qualitative, using sociopragmatic studies. The data sources of this research are E-sports commentators' utterances which are expressive and contain special forms of vocabulary. Data collection techniques using listening and note-taking techniques. Data analysis using contextual analysis methods. The results of this study are the findings of expressive speech acts in the E-Sports commentator's speech which are divided into ten peech functions, namely: thanking, disgust, justifying, hoping, praising, apologizing, congratulating, complaining, regretting, and insinuating. In addition, there were 58 data orms of special vocabulary classified into 4 forms, namely, singular, affixation, abbreviation/shortening, and compound. The vocabulary data is divided into two categories of meaning, namely the denotative meaning of 32 data and the connotative meaning of (26) data.